A new boosting algorithm for provably accurate unsupervised domain adaptation. Issue 1 (April 2016) - Habrard, Amaury; Peyrache, Jean-Philippe; Sebban, Marc
Abstract Domain adaptation (DA) is a new learning framework dealing with learning problems where the target test data are drawn from a distribution different from the one that has generated the learning source data. In this article, we introduce self-labeling domain adaptation boosting (SLDAB), a new DA algorithm that falls both within the theory of DA and the theory of Boosting, allowing us to derive strong theoretical properties. SLDAB stands in the unsupervised DA setting where labeled data are only available in the source domain. To deal with this more complex situation, the strategy of SLDAB consists in jointly minimizing the empirical error on the source domain while limiting the violations of a natural notion of pseudo-margin over the target domain instances. Another contribution of this paper is the definition of a new divergence measure aiming at penalizing models that induce a large discrepancy between the two domains, reducing the production of degenerate models. We provide several theoretical results that justify this strategy. The practical efficiency of our model is assessed on two widely used datasets.